2022
DOI: 10.1016/j.jhep.2021.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin-α reduces gut-derived inflammation and mucin degradation in cirrhosis and encephalopathy: RIFSYS randomised controlled trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 44 publications
6
97
0
1
Order By: Relevance
“…Changes in the gut microbiota profile are observed in any tract of the gastrointestinal system, including the oral mucosa [ 151 ]. Translocation to the gut of oral pathogens capable of degrading intestinal mucus has recently been demonstrated in cirrhotic patients with hepatic encephalopathy, suggesting that the oral-gut–liver axis is involved in the pathogenesis of liver disease complications [ 152 ].…”
Section: The Gut–liver Axismentioning
confidence: 99%
“…Changes in the gut microbiota profile are observed in any tract of the gastrointestinal system, including the oral mucosa [ 151 ]. Translocation to the gut of oral pathogens capable of degrading intestinal mucus has recently been demonstrated in cirrhotic patients with hepatic encephalopathy, suggesting that the oral-gut–liver axis is involved in the pathogenesis of liver disease complications [ 152 ].…”
Section: The Gut–liver Axismentioning
confidence: 99%
“…Therefore, rifaximin-activated PXR may recover the intestinal barrier function by reducing intestinal permeability and gut endotoxin leakage in patients with cirrhosis. A recent clinical report also showed that rifaximin has a role in gut barrier repair by ameliorating bacterial translocation and systemic endotoxemia in patients with cirrhosis [ 45 ], which may improve the hepatic reserve.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence supports the hypothesis that rifaximin could exert other beneficial effects in addition to its antimicrobial effects, as previously described. 20,[22][23][24] In fact, alcohol exerts direct toxicity on the liver and promotes intestinal dysbiosis, which favours liver dysfunction. 25 Alcohol changes the composition and biodiversity of normal flora, which increases the levels of lipopolysaccharide and other toxic substances, leading to an increase in intestinal permeability.…”
Section: Adverse Effects Of Rifaximinmentioning
confidence: 99%